2014
DOI: 10.1016/j.neuron.2014.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-Related Neural Activity Regulates the Structure of Vascular Networks in the Cerebral Cortex

Abstract: SUMMARY Neurovascular interactions are essential for proper brain function. While the effect of neural activity on cerebral blood flow has been extensively studied, whether neural activity influences vascular patterning remains elusive. Here, we demonstrate that neural activity promotes the formation of vascular networks in the early postnatal mouse barrel cortex. Using a combination of genetics, imaging, and computational tools to allow simultaneous analysis of neuronal and vascular components, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(161 citation statements)
references
References 64 publications
10
150
0
1
Order By: Relevance
“…Our preliminary data show that distinct brain regions exhibited different cell body density and nuclei-vascular distance profiles. Such quantitative analysis may reveal important structural or pathological features of the vascular network or cell-vascular interactions in normal or diseased brain tissues (41)(42)(43)(44). Together, these results demonstrate that stochastic electrotransport may be useful for rapid and quantitative 3D phenotyping of organ-scale biological systems.…”
Section: Application Of Stochastic Electrotransportmentioning
confidence: 82%
“…Our preliminary data show that distinct brain regions exhibited different cell body density and nuclei-vascular distance profiles. Such quantitative analysis may reveal important structural or pathological features of the vascular network or cell-vascular interactions in normal or diseased brain tissues (41)(42)(43)(44). Together, these results demonstrate that stochastic electrotransport may be useful for rapid and quantitative 3D phenotyping of organ-scale biological systems.…”
Section: Application Of Stochastic Electrotransportmentioning
confidence: 82%
“…These anti-angiogenic effects were associated with hypoxic conditions in the corresponding overstimulated brain regions, which in turn was accompanied dendritic spine loss. A separate study (Lacoste et al, 2014) employed both enhanced and decreased whisker experience, and found that blood vessel patterning in barrel cortex was modulated as a result: vascular density and branching were diminished in response to whisker deprivation whereas the same metrics were enhanced upon whisker stimulation. These findings indicate that the organization of the neurovascular bed is modulated in the wake of sensory experience, and suggest that brain oxygen levels (which are a derivative of brain vascularization) can in fact form a limiting factor to synaptic plasticity.…”
Section: ) From Synaptic Activity To Vascular Plasticitymentioning
confidence: 99%
“…PDGF-BB-mediated induction of chemotaxis and mitogenesis in vascular smooth muscle cells requires PLAT, linking PDGF-B to yet another vasculature modulator (Herbert et al, 1997). Because these genes are expressed in an activitydependent manner (based on (Vallès et al, 2011)), pathways such as these could well orchestrate blood vessel patterning to suit the needs of neuronal circuits (Lacoste et al, 2014;Whiteus et al, 2014).…”
Section: 1) Molecules Of Neurovascular Plasticitymentioning
confidence: 99%
“…Ce n'est que très récemment que la contribution de l'activité neuronale au développement cérébrovasculaire a été démontrée, à la suite de notre étude dans le laboratoire de Chenghua Gu à l'Université Harvard [11]. Il est important d'évoquer la parution, quelques mois avant notre article, d'une étude rapportant l'effet néfaste de l'hyperactivité neuronale sur la maturation des vaisseaux cérébraux [12].…”
Section: Rôle De L'activité Neuronale Dans La Maturation Des Vaisseauunclassified